Electrical Impedance Tomography Accurately Reflects Regional Ventilation Distribution Compared With Computed Tomography in Non-Intubated Subjects. - Morais, Caio C.A.; Rattes, Catarina; Rocha, Taciano; Hirota, Adriana S.; Souza, Renata P.; Souza, Rodrigo V.C.; Andrade, Erika A.M.; Kajiyama, Carolina E.; Olegário, Tayran M.M.; Guzman, Ana I.A.; de Alencar, Nadja R.G.; Brandão, Daniella C.; et al. (Respiratory Care, 2026)
Background: Electrical impedance tomography (EIT) is a validated tool for monitoring patients receiving mechanical ventilation. The performance of EIT in quantifying regional ventilation in non-intubated subjects remains unknown. We aimed to compare the agreement of EIT regional ventilation distribution with computed tomography (CT) scans in spontaneously breathing subjects. In addition, we assessed the influence of patient-related factors on measurement error and the reproducibility of EIT ventilation quantification. Methods: Healthy adults under spontaneous breathing underwent simultaneous EIT measurements and whole-lung CT scans. Changes in thoracic impedance by EIT and air content by CT during end-expiratory and end-inspiratory pauses were compared using standard anterior–posterior and right–left regions of interest (ROI). The intra- and inter-evaluators reproducibility of ventilation distribution was assessed using 2 trained evaluators. Results: EIT and CT images were collected from 32 subjects. The best combination of bias and limits of agreement for regional ventilation distribution was achieved with a CT lung length of 15 cm. At this lung length, we found a bias of 0.80% with limits of agreement ranging from −9.26% to 10.87% in the posterior ROI and a bias of −1.33% with limits of agreement from −9.15% to 6.47% in the right ROI. Biological sex, body mass index, fat percentage, or thoracic and abdominal circumferences did not affect EIT–CT measurement differences. The maximum intra- and inter-examiner bias was below 1.5%, with limits of agreement lower than 10% for both antero-posterior and right–left lung regions. Conclusions: EIT was a valid and reliable instrument for assessing ventilation distribution in non-intubated subjects during spontaneous breathing.